Analisis Beberapa Jenis PLTS di Khatulistiwa Menggunakan Prototype alat ukur PV - Ananto, Rhezal Agung; Handani, Galuh Prawestri Citra; Santoso, Asfari Hariz; Gumilang, Binar Surya (Elposys: Jurnal Sistem Kelistrikan, 2023)
Photovoltaic is employed to support the national electricity energy blending policy as an additional component of renewable energy. Efficient energy monitoring is utilized to understand the efficiency, energy requirements, and performance of Photovoltaic. This research aims to analyze the performance of a standalone Photovoltaic system. The study considers various parameters such as PV size, load, and charge controller. Additionally, it involves designing a monitoring tool used for the analysis of Photovoltaic performance. Performance measurements are conducted by comparing Photovoltaic systems of different sizes. Furthermore, performance measurements are compared with different types of charge controllers. To assess performance, solar energy is measured at various times using a solar power meter. The solar power meter is then used to analyze the research's performance. Energy monitoring involves measuring voltage, current, power, and energy using Atmega328p. The measurement data is utilized to evaluate system efficiency and design future systems. Monitoring is carried out directly on Photovoltaic systems in the equatorial region. This research measures solar energy, energy produced by Photovoltaic systems, and energy consumed by loads. Energy monitoring focuses on observing solar and Photovoltaic energy during sunlight hours (morning-evening). The analysis results can be utilized for designing efficient Photovoltaic systems in the future..